Qualitative Release and Exposure Assessment on the risk of HPAI transmission between sector 4 farms and between sector 3 and sector 4 farms in Kenya - Onkundi, Dennis; Bett, Bernard; Costard, Solenne; Omore, Amos; Zepeda, Cristobal (International Food Policy Research Institute, 2010)
This study assessed the risk of transmission of highly pathogenic avian influenza (HPAI) between backyard poultry (S4) farms and between S4 and semi-commercial (S3) farms in Kenya. It was designed to complement findings of a study that had been conducted in 2007 by the DVS and FAO to evaluate the risk of introduction of the disease into the country. It followed the OIE risk analysis framework where release, exposure and consequence assessments are done successively and their risk parameter estimates combined to obtain an overall risk estimate for a given pathway. Risk questions were formulated in a stakeholder workshop that was convened at ILRI in Nairobi on 2-3 October 2008.